Correlations between morphological features of intracoronary thrombi and left ventricular structure and function in patients with ST-segment elevation myocardial infarction - Zerbino, D. D.; Besh, D. I.; Sokolov, M. Yu.; Besh, O. M. (Medicni Perspektivi, 2020)
The majority of cases of acute ST-elevation myocardial infarction (STEMI) are caused by the rupture of an atherosclerotic plaque and subsequent thrombus formation. The study of clot structure may be important for the prediction of further course of the disease. The study included 100 patients with STEMI who underwent primary percutaneous coronary intervention (PCI) with manual thromboaspiration within the first 12 hours after the onset of symptoms. Sufficient aspiration material for histological examination was obtained in 97 patients. These intracoronary thrombi were investigated macroscopically and microscopically. Subsequently, correlations between morphological structure of thrombi and structural and functional features of the myocardium after revascularization were analyzed. Pathological QS pattern was detected in 45 (46.39±5.06%) patients. Peripheral infiltration of intracoronary thrombus with neutrophils was the only morphological feature associated with the presence of QS (r= -0.36; p<0.001). The mean left ventricular ejection fraction (LVEF) measured during echocardiography was 48.34±9.39%. Positive and significant correlation was found between LVEF and peripheral infiltration of intracoronary thrombus with neutrophils (r=0.37; p<0.001), while negative correlation was found between LVEF and presence of microchannels within the clot (r= -0.27; p<0.01). The mean total segmental left ventricular contractility index at the time of hospital discharge was 1.38 [1.25; 1.63]. This index negatively correlated with neutrophil infiltration (r= -0.37; p<0.001), and positively – with the presence of microchannels in the obtained clot samples (r=0.26; p=0.01). Signs of left ventricular aneurysm formation before discharge from the hospital were found in 15 (15.46±3.67%) patients. A significant negative correlation was found between this parameter and the presence of peripheral neutrophil infiltration of intracoronary thrombi (r= -0.32; p<0.01). The presence of peripheral infiltration of intracoronary thrombi with neutrophil leukocytes was associated with better left ventricular systolic function and less likely hood of development of left ventricular aneurysm or electrocardiographic QS pattern. The formation of microchannels within the clot was associated with poorer recovery of systolic cardiac function.